Determination of maximum in place air void for impermeable hot mix asphaly pavement - Hainin, Mohd. Rosli; Brown, E. Ray (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2006)
Obtaining adequate density is a major requirement in the construction of hot mix asphalt (HMA) pavements. Density is very much related to the air voids. As air voids increase, the density decreases. This study determined the maximum in-place air void for impermeable HMA pavements. A total of 497 core samples were obtained from 57 different ongoing HMA construction projects immediately after rolling. Nine different mix types utilised in this study were fine dense-graded 9.5 mm, 12.5 mm, 19.0 mm and 25.0 mm nominal maximum aggregate size (NMAS) mixes, coarse dense-graded 9.5 mm, 12.5 mm and 19.0 mm NMAS mixes, and Stone Matrix Asphalt (SMA) 9.5 mm and 25.0 mm NMAS mixes. Bulk specific gravity of each core sample was determined using both American Association of State Highways and Transportation Officials (AASHTO) T 166 and vacuum sealing methods, and permeability was determined using American Society for Testing and Materials (ASTM) PS129-01. This study found that in-place air void content was the most significant factor affecting permeability. The in-place air voids for dense-graded HMA pavements should not exceed 7%